Ο στιγματισμός των συμμετεχόντων στην εκπαιδευτική διαδικασία: η περίπτωση των εκπαιδευτικών προσχολικής ηλικίας - Παρασκευοπούλου-Κόλλια Ευφροσύνη-Άλκηστη (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
The educational systems have been permitted by the modern social shapings to distinguish the individuals at the period of school age in educated and not, to evaluate them via the titles that they grant and tο place them in the professional-social hierarchy. Examining the subject of teachers’ choice of profession from the side of experience, payment and environment, the relation between the more inferior social layers and the instructive profession is once again revealed. In other words, the professional choices are limited for concrete students and immediately connected with their social origin. Their choice to follow a concrete profession is completely connected with the parameters that structure their life. The teacher accepts hurtful opinions from society, is forced to face cognitive divergences of views, feels the need to upgrade her/his scientific training and, often, s/he adopts a negative and low self-esteem. A basic characteristic stigmatizing teachers is the uncertainty for their social place (status).